PERANCANGAN TYPEFACE “MANTINGAN FONT” DAN SIGN SYSTEM BERBASIS ORNAMEN MASJID MANTINGAN DI KABUPATEN JEPARA - Setiawan, Agus; Yanuarsari, Dzuha Hening (Institut Bisnis dan Teknologi Indonesia, 2022)
The Mantingan Mosque is one of the cultural heritages of ancient Islam and is one of the tourism assets in Jepara Regency. The Mantingan Mosque in Jepara has several ornamental designs that are applied to several sides of the mosque walls. The Mantingan Mosque also has a characteristic ornament design that still has acculturation elements of Chinese, Hindu, Buddhist and Javanese cultures. These ornaments were then inspired to be developed into a typeface design concept which in it has an anatomical element of an ornament character where the construction is based on typeface design rules. The visual concept of this typeface design is obtained from the results of research conducted on respondents who are engaged in the design field. Then the typeface is designed on a digital basis which is packaged into a font pack with the name “Mantingan Font.otf” format which can be installed and used on a PC (Personal Computer). The designed typeface is then socialized to partners (Mantingan mosque administrators) to be further developed in the form of an application on the media sign system. The purpose of this design is to develop and support the context of the information system (sign system) at the Mantingan mosque in Jepara Regency as religious tourism. The research method used is descriptive-quantitative supported by factual field data and research that has been carried out supported by ATUMICS approach.